Structural View and Substrate Specificity of Papain-like Protease from Avian Infectious Bronchitis Virus - Kong, Lingying (J Biol Chem, 2015)
Papain-like protease (PLpro) of coronaviruses (CoVs) carries out proteolytic maturation of non-structural proteins that play a role in replication of the virus and performs deubiquitination of host cell factors to scuttle antiviral responses. Avian infectious bronchitis virus (IBV), the causative agent of bronchitis in chicken that results in huge economic losses every year in the poultry industry globally, encodes a PLpro. The substrate specificities of this PLpro are not clearly understood. Here, we show that IBV PLpro can degrade Lys(48)- and Lys(63)-linked polyubiquitin chains to monoubiquitin but not linear polyubiquitin. To explain the substrate specificities, we have solved the crystal structure of PLpro from IBV at 2.15-Å resolution. The overall structure is reminiscent of the structure of severe acute respiratory syndrome CoV PLpro. However, unlike the severe acute respiratory syndrome CoV PLpro that lacks blocking loop (BL) 1 of deubiquitinating enzymes, the IBV PLpro has a short BL1-like loop. Access to a conserved catalytic triad consisting of Cys(101), His(264), and Asp(275) is regulated by the flexible BL2. A model of ubiquitin-bound IBV CoV PLpro brings out key differences in substrate binding sites of PLpros. In particular, P3 and P4 subsites as well as residues interacting with the β-barrel of ubiquitin are different, suggesting different catalytic efficiencies and substrate specificities. We show that IBV PLpro cleaves peptide substrates KKAG-7-amino-4-methylcoumarin and LRGG-7-amino-4-methylcoumarin with different catalytic efficiencies. These results demonstrate that substrate specificities of IBV PLpro are different from other PLpros and that IBV PLpro might target different ubiquitinated host factors to aid the propagation of the virus.